PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN MASAYARAKAT DI KANTOR KECAMATAN KENJERAN SURABAYA - Marhadika, Alfa Sakinata (JPAP: Jurnal Penelitian Administrasi Publik, 2016)
Public service is one of the important tasks that can not be ignored by the localgovernment. As an institution, the public service Kenjeran District of Surabaya ensure thesustainability of the State administration involving policy development and resourcemanagement services that come from and to the public interest or the public. The purposein this study to determine the effect of service quality to satisfaction of the people in theDistrict Office Kenjeran Surabaya. The data used in this study are primary data (from thequestionnaire) with samples taken 100 people. While the analytical techniques used is byusing multiple linear regression. The test results showed the influence of variablessimultaneously consists of physical evidence, reliability, responsiveness, assurance andempathy affect the satisfaction of the people in the District Office Kenjeran Surabaya.These results are supported by the acquisition of the correlation coefficient of 71.5% wasobtained, indicating that the correlation or relationship between these variables to thesatisfaction of the people have a close relationship. Partial test results show the variablequality of service consisting of variable physical evidence, reliability, responsiveness,assurance and empathy positive and significant impact on the satisfaction of the people inthe District Office Kenjeran Surabaya. Sedagnkan variables that have a dominant influenceon people's satisfaction at the District Office Kenjeran Surabaya is responsiveness byhaving the partial determination coefficient than other variables.Keywords: Physical Evidence, Reliability, Responsiveness, Assurance, Empathy andCommunity Satisfaction